Development of gummy jelly mixed with Thunbergia laurifolia Linn. extract for reducing breath alcohol concentration - Kitpot, Thanapon (Food and Applied Bioscience Journal, 2020)
This study aimed to develop gummy jelly mixed with Thunbergia laurifolia Linn. extract for reducing breath alcohol content. Three levels of Thunbergia laurifolia Linn. extract gummy jelly; 5, 10 and 15% (w/w) were developed. The optimum formula of gummy jelly from consumer test consisted of sugar 30%, glucose syrup 28%, gelatin 8%, citric acid 2% and Thunbergia laurifolia Linn. extract 10%. The texture properties of the gummy jelly were as follow: hardness 702.17 ± 49.70 g, cohesiveness 0.95 ± 0.02, springiness 0.93 ± 0.02, gumminess 644.17 ± 47.09 and chewiness 603.33 ± 43.84 g. Color values (L*, a* and b*) of gummy jelly were 34.70 ± 1.31, 1.63 ± 0.28 and 5.85 ± 0.41, respectively. Water activity (aw) of the final product was 0.77 ± 0.01. The microbial properties were compatible with the Thai jelly standard. From the preliminary in vitro study of the effect of gummy jelly on the reduction of alcohol content measured by hydrometer, it was found that gummy jelly mixed with Thunbergia laurifolia Linn. could reduce alcohol content in the breath. Preliminary efficacy test was conducted in 15 volunteers, with an average age of 22.4 ± 0.9 years. It was found that eating 5 pieces (5.0 ± 0.5 g per one piece) of gummy jelly could reduce the amount of alcohol in the breath from 0.164 ± 0.002% to 0.000 ± 0.001% by using a breath alcohol tester (reported in term of %BAC, blood alcohol content). This research demonstrated the potential of gummy jelly mixed with Thunbergia laurifolia Linn. extract that could help to reduce breath alcohol concentration which just lower the risk of accident rates after drinking alcoholic beverages.